Las causas del derecho, por Rodolfo Luis Vigo (h.), prólogo de Georges Kalinowski, Buenos Aires, Abeledo-Perrot, 1983, 182 pp. - Massini Correas, Carlos I. (1983)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina